Zákon Č. 311/2001 Z.z. z 2. júla 2001 Zákonník práce ...
Zákon Č. 311/2001 Z.z. z 2. júla 2001 Zákonník práce v znení Zákona Č. 165/2002 Z.z., Zákona Č. 408/2002 Z.z. a Zákona z 21. mája 2003 + Dôvodová správa k novele Zákonníka práce.